A shift of the perceptual attributes of color due to the manifestation of the simultaneous contrast effect on a display. Issue 4 (7th April 2020) - Hajdek, Krunoslav; Budimir, Ivan; Matijević, Mile
Abstract: This research shows the effect of simultaneous contrast on a design solution that generates it, and it also shows how its manifestation affects the shift of perception attributes of the observer's color. In the conducted research, 55 subjects had to harmonize the primary stimuli from the reproduction obtained with the help of digital printing technology, with the primary stimuli presented on two computer screens. As a visual harmonization technique, simultaneous binocular harmonization was used. The primary stimuli were made achromatic, with a 50% Raster Tone value (RTV), and are surrounded by achromatic secondary stimuli whose values increase in steps from 10% RTV up to 100% RTV. A shift in the perceptual attributes of color has been shown with the help of the CIEDE2000 system. Using ANOVA with repeated‐measures and Fisher's post hoc analysis, statistically significant differences were found between the perceived means of shift in the Δ C 00 chroma and Δ L 00 lightness on defined samples on both computer screens, while in the case of the Δ H 00 hue, no statistically significant differences were observed. The research also determined colorimetric differences in the Δ E 00 color difference. Moreover, the student's t test was used to determine that the effect is stronger when manifested on the Lenovo computer than on the Asus computer screen ( P < .05).